High-Resolution Vertical Observations of Phytoplankton Groups Derived From an in-situ Fluorometer in the East China Sea and Tsushima Strait - Xu, Qian; Wang, Shengqiang; Sukigara, Chiho; Goes, Joaquim I.; Gomes, Helga do Rosario; Matsuno, Takeshi; Zhu, Yuanli; Xu, Yongjiu; Luang-on, Jutarak; Watanabe, Yuji; Yoo, Sinjae; Ishizaka, Joji (Frontiers in Marine Science, 2022)
Vertical distribution of phytoplankton composition in the East China Sea (ECS) and Tsushima Strait (TS) was highly variable in the region where the Changjiang River diluted water (CDW), Kuroshio water (KW), and Tsushima water (TW) intersected. An in-situ multiple excitation fluorometer was used to obtain the high-resolution phytoplankton groups data from every meter of the water column. Sharp differences were noted in the distribution of phytoplankton groups in the CDW, KW, and TW. In the CDW, brown algae were generally present ~60% of all depths with exception of subsurface chlorophyll-a maximum (SCM), whereas cyanobacteria (>40%) and green algae plus cryptophytes (>40%) were found above and below the SCM, respectively. In TW, where chlorophyll a (CHL) was lower than in the CDW, brown algae predominated the water column (>60%) and SCM (>80%), except the surface layer where cyanobacteria dominated. In KW, a high fraction of cyanobacteria (>40%) extended up to 40 m, while brown and green algae dominated (>60%) the deeper waters below 40 m at western and eastern stations, respectively. These results can be further related to water property and nutrient concentration of the water masses in each region. This new data show that the in-situ multiple excitation fluorometer can be a powerful tool to estimate high-resolution vertical profiles of phytoplankton groups on a large scale in marine environments.